A novel passive left heart platform for device testing and research. Issue 4 (April 2015) - Leopaldi, A.M.; Vismara, R.; van Tuijl, S.; Redaelli, A.; van de Vosse, F.N.; Fiore, G.B.; Rutten, M.C.M.
Abstract Integration of biological samples into in vitro mock loops is fundamental to simulate real device's operating conditions. We developed an in vitro platform capable of simulating the pumping function of the heart through the external pressurization of the ventricle. The system consists of a fluid-filled chamber, in which the ventricles are housed and sealed to exclude the atria from external loads. The chamber is connected to a pump that drives the motion of the ventricular walls. The aorta is connected to a systemic impedance simulator, and the left atrium to an adjustable preload. The platform reproduced physiologic hemodynamics, i.e. aortic pressures of 120/80 mmHg with 5 L/min of cardiac output, and allowed for intracardiac endoscopy. A pilot study with a left ventricular assist device (LVAD) was also performed. The LVAD was connected to the heart to investigate aortic valve functioning at different levels of support. Results were consistent with the literature, and high speed video recordings of the aortic valve allowed for the visualization of the transition between a fully opening valve and a permanently closed configuration. In conclusion, the system showed to be an effective tool for the hemodynamic assessment of devices, the simulation of surgical or transcatheter procedures and for visualization studies.